O potencial pedagógico dos espaços não formais da cidade de Manaus - Maciel, Hiléia Monteiro (2013)
The non-formal settings increasingly gaining prominence, because the features present in these locations arouse curiosity, emotions and promotes the exchange of knowledge sociocultural. The objective of this research was to analyze the pedagogical potential for Teaching Science in ten non-formal institutionalized spaces in the city of Manaus – AM. The areas investigated were: Samaúma State Park, Mindu Municipal Park, City of the Children Park, Amazonian Museum, Seringal Vila Paraíso Museum, Adolpho Ducke Botanical Garden/ Museum of the Amazonian, Lagoa do Japiim Municipal Park, Bilhares Municipal Park, CIGS Zoo, Science Grove. To achieve our goal we use the method called multi case that has a qualitative descriptive nature. The data collection instruments were used observation, questionnaires and interviews with the Manager and Responsible for the Pedagogical Area. The analysis technique chosen for this research was the analysis of the content. Compared to City of the Children Park, analyze the Bylaws and interview Responsible for the Pedagogical Area, realize that there isn’t a concordance between them. In the case of the Adolpho Ducke Botanical Garden / Museum of the Amazonian verified the agreement between the Statute and the speech of the Manager. The Seringal Vila Paraíso Museum provides a trip in the imagination to understand how it worked closely the process of extracting latex (milk) of rubber and what life was like rubber and the rubber barons. In Mindu Park even though the presence of common schools, we realized that there isn’t specific pedagogical activities that teachers can develop a more focused activity. For the Amazonian Museum found the harmony between theory and practice, in other words, what is found in documents regimental of the museum and its everyday practices. For the Samaúma State Park, what we found was the non-compliance with their articles. What we found is that the Samaúma State Park gives more emphasis to recreation and environmental interpretation and not the development of educational activities. Confronting the formal documents, speech manager and their observations, the Lagoa do Japiim Park, works with other perspectives, beyond that for which it was created. By analyzing various documents of the Bilhares Municipal Park realized that this was created with the goal of providing leisure and entertainment to the public that visit. In no time we see official documents indicating that the park should develop other types of activities. Analyze the documents and projects that develops CIGS Zoo, we realize that there isn’t project that is directly (or indirectly) for teaching. During our observations and analyzing the official documents of Forest Science, realize that these are in line with the proposed objectives for which it was created, that is, besides disseminating scientific knowledge allows its visitors a moment of leisure and entertainment. In the ten Non-Formal Institutionalized Settings, three spaces have pedagogical potential for Science Teaching (Amazon, Adolpho Ducke Botanical Garden / Museum of the Amazonian and Science Grove), five with reasonable prospects for teaching (Mindu Park, City of the Children Park, Lagoa do Japiim Municipal Park, CIGS Zoo and Bilhares City Park) and two with no prospect (Samaúma State Park, Seringal Vila Paraíso Museum).